2019
DOI: 10.1103/physrevb.100.184312
|View full text |Cite
|
Sign up to set email alerts
|

Quantum many-body scars from magnon condensation

Abstract: We study the eigenstate properties of a nonintegrable spin chain that was recently realized experimentally in a Rydberg-atom quantum simulator. In the experiment, long-lived coherent manybody oscillations were observed only when the system was initialized in a particular product state. This pronounced coherence has been attributed to the presence of special "scarred" eigenstates with nearly equally-spaced energies and putative nonergodic properties despite their finite energy density. In this paper we uncover … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
114
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 62 publications
(144 reference statements)
11
114
0
Order By: Relevance
“…By contrast, in the strongly interacting Rydberg atom chain initialized in the Néel state, quantum dynamics remains concentrated around a small subset of states in the many-body Hilbert space, thus it is effectively "semiclassical" [21]. While recent works [26,27] have shown that revivals can be significantly enhanced by certain perturbations to the system, a general understanding of the conditions that allow scars to occur in a many-body quantum system is still lacking.The observation of periodic dynamics was linked to the existence of atypical eigenstates at evenly spaced energies throughout the spectrum of the many-body system [20,28,29]. Similar phenomenology was previously found in the non-integrable AKLT model [30,31], where highly-excited eigenstates with low entanglement have been analytically constructed.…”
supporting
confidence: 68%
“…By contrast, in the strongly interacting Rydberg atom chain initialized in the Néel state, quantum dynamics remains concentrated around a small subset of states in the many-body Hilbert space, thus it is effectively "semiclassical" [21]. While recent works [26,27] have shown that revivals can be significantly enhanced by certain perturbations to the system, a general understanding of the conditions that allow scars to occur in a many-body quantum system is still lacking.The observation of periodic dynamics was linked to the existence of atypical eigenstates at evenly spaced energies throughout the spectrum of the many-body system [20,28,29]. Similar phenomenology was previously found in the non-integrable AKLT model [30,31], where highly-excited eigenstates with low entanglement have been analytically constructed.…”
supporting
confidence: 68%
“…Recently, however, several exceptions have been discovered [34][35][36][37][38]. Systems with constrained dynamics [39,40] are an especially promising avenue where non-thermal eigenstates, dubbed scar states, can occur [33,[41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Several works investigated the possibility of mimicking similarly localized behavior without explicitly breaking translation invariance [25][26][27][28][29][30][31][32][33], as well as the possibility of intermediate behavior, such as the existence of a small number of ETH-violating eigenstates within an otherwise generic spectrum of states [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Recently, the authors of the present paper, following earlier work on dipole-conserving random circuits [49], identified a novel mechanism for such non-ergodic behavior, dubbed Hilbert space fragmentation [50,51].…”
mentioning
confidence: 99%